2010
DOI: 10.1007/s10147-010-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, placebo-controlled trial of zoledronic acid in bony metastatic bladder cancer

Abstract: Zoledronic acid therapy decreased the incidence of SREs and improved the 1-year survival rate of patients with bone metastases from bladder cancer, potentially through its anticancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 29 publications
0
78
0
Order By: Relevance
“…Denosumab acts directly on RANK-expressing cancer cells including breast, prostate and melanoma cells (Jones et al, 2006). Zoledronic acid has a potential positive impact on OS in several tumour types with osteolytic bone disease such as NSCLC (Zarogoulidis et al, 2009), bladder carcinoma (Zaghloul et al, 2010), RCC (Saad and Eastham, 2010;Beuselinck et al, 2012;Keizman et al, 2012;Broom et al, 2014) and multiple myeloma (Morgan et al, 2010). Evidence of anti-tumoral efficacy of denosumab has been shown in prostate cancer at high risk for the development of BM: denusomab can delay the development of BM by several months (Smith et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Denosumab acts directly on RANK-expressing cancer cells including breast, prostate and melanoma cells (Jones et al, 2006). Zoledronic acid has a potential positive impact on OS in several tumour types with osteolytic bone disease such as NSCLC (Zarogoulidis et al, 2009), bladder carcinoma (Zaghloul et al, 2010), RCC (Saad and Eastham, 2010;Beuselinck et al, 2012;Keizman et al, 2012;Broom et al, 2014) and multiple myeloma (Morgan et al, 2010). Evidence of anti-tumoral efficacy of denosumab has been shown in prostate cancer at high risk for the development of BM: denusomab can delay the development of BM by several months (Smith et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its bone-protective effects, zol has demonstrated clinically meaningful anticancer activity in multiple cancer settings, including that of multiple myeloma [10][11][12][13][14][15] . In particular, results from the large U.K. Medical Research Council (mrc) Myeloma ix trial demonstrated a significant overall survival (os) benefit for zol compared with the weaker oral bisphosphonate clodronate in patients with newly diagnosed multiple myeloma 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence is demonstrating that zol also improves non-skeletal outcomes in cancer patients with advanced bone disease 10,[13][14][15] . Those benefits might be based primarily on two potential mechanisms:…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[13][14][15][16][17] Recently, preclinical and clinical data have also demonstrated anticancer effects of bisphosphonates in breast and other cancer types. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The prevention and treatment of bone loss with upfront (initiated simultaneously with letrozole) versus delayed (initiated with a decrease in T score to <À2 or occurrence of clinical nontraumatic fracture) zoledronic acid in early breast cancer patients receiving letrozole was evaluated in 3 similarly designed, geographically diverse studies (Z-FAST; ZO-FAST; E-ZO-FAST) and in the similarly-designed N03CC study. 15 Interim (<36 months follow-up) results from the former 3 studies indicate that upfront rather than delayed-start zoledronic acid is significantly more effective in preventing bone loss.…”
Section: Introductionmentioning
confidence: 99%